Motivations of international students from Indonesia, Thailand, and the Philippines in selecting teacher education programs - Fihris, Fihris; Nasikhin, Nasikhin; Naifah; Sofa Muthohar (Journal of International Students, 2024)
In this study, we examined the motivations of students from Indonesia, Thailand, and the Philippines in choosing to pursue undergraduate teacher education programs. Through a narrative inquiry approach, we collected data using focus group discussions and in-depth discussions with international student representatives from the three countries. Findings show that the common motivation of students from the three countries in choosing a teacher education study program was to improve the quality of education in their home countries and form a better next generation. However, there is a fundamental difference in the motivation behind their choices. Filipino students view teaching as a challenging and dynamic job, whereas Indonesian students are driven by religious calling, parental encouragement, and attractive work-hour flexibility.